Relative configuration of Cys‐Pro ester peptides in thioester formation. (15th February 2022) - Kawakami, Toru; Sasakura, Eri; Miyanoiri, Yohei; Hojo, Hironobu
Abstract : A peptide containing a cysteinyl prolyl ester (CPE) moiety at the C‐terminus (CPE peptide) was transformed into a diketopiperazine (DKP) thioester via an intramolecular N–S acyl shift reaction and was then used for peptide ligation. The difference in reactivity between the CPE peptide stereoisomers was examined. In reactions of the CPE peptides that contained L‐Cys‐L‐Pro or D‐Cys‐D‐Pro, the desired DKP thioester was formed at the preceding amino acid residue. On the other hand, in reactions of the CPE peptides that contained D‐Cys‐L‐Pro or L‐Cys‐D‐Pro, a thiolactone was formed at the C‐terminal prolyl ester, and the ligation occurred at the C‐terminal Pro residue. Using this reaction, it was possible to efficiently prepare a cyclic peptide. Abstract : A peptide with a cysteinyl prolyl ester (CPE) moiety at the C‐terminus was transformed into a thioester. Herein, the differences in the reactivity for the CPE peptide stereoisomers were investigated. In reactions using either L‐Cys‐L‐Pro or D‐Cys‐D‐Pro in the CPE, the desired diketopiperazine thioester was formed at the preceding amino acid residue, but in the reactions of the D‐Cys‐L‐Pro or L‐Cys‐D‐Pro stereoisomers, the thiolactone was formed at the C‐terminal prolyl ester.